Streptococcus intermedius Causing Necrotizing Pneumonia in an Immune Competent Female: A Case Report and Literature Review - Hannoodi, Faris (Case Rep Pulmonol, 2016)
We report a case of a 52-year-old immunocompetent Caucasian female treated for necrotizing Streptococcus intermedius pneumonia and review available literature of similar cases. Our patient presented with respiratory failure and required hospitalization and treatment in the intensive care unit. Moreover, she required surgical drainage of right lung empyema as well as decortication and resection. The review of literature revealed three cases of S. intermedius pneumonia, one of which was a mortality. Comparison of the published cases showed a highly varied prehospital course and radiological presentations, with a symptomatic phase ranging from 10 days to five months. Radiological findings varied from an isolated pleural effusion to systemic disease with the presence of brain abscesses. Immunocompetence appears to correlate well with the overall prognosis. In addition, smoking appears to be an important risk factor for S. intermedius pneumonia. In 2 (50%) of cases, pleural fluid analysis identified S. intermedius. In contrast, no organism was found in our patient, necessitating the acquisition of lung tissue sample for the diagnosis. In conclusion, both medical and surgical management are necessary for effective treatment of S. intermedius pneumonia. The outcome of treatment is good in immunocompetent individuals.